Comparison of physical profile of Malaysian basketball and netball players by playing position - Soh, Kim Geok; Soh, Kim Lam; Husain, Ruby; Omar Fauzee, Mohd Sofian; Yusof, Aminuddin; Jamalis, Marjohan (Africa Association for Health, Physical Education, Recreation, Sport and Dance, 2009)
The aim of the research is to compare the physical profile of Malaysian women basketball and netball players. The physical profile measures were height, body mass, and body fat. The subjects were divided into two groups based on their playing performance and positions. The playing performance consisted of elite/senior, junior, and reserve, while for playing positions were forward/attack, centre, and guard/defence. The percentage of body fat was determined by means of skinfold measurement at seven different locations. Results showed that there were significant differences in body fat percentage between basketball and netball players (t (63) = –4.20, p<0.01). The elite/senior basketball players had the lowest body fat percentage, while the guard/defence basketball players were the shortest and have the lowest body fat percentage. In conclusion, Malaysian basketball players were found to be physically bigger and thus more domineering having been in a contact sport as compared to the Malaysian netball players.